Transoral surgery using the Flex Robotic System: Initial experience in the United States. Issue 11 (10th October 2018) - Persky, Michael J.; Issa, Mohamad; Bonfili, Jennifer R.; Goyal, Neerav; Goldenberg, David; Duvvuri, Umamaheswar
Abstract: Background: This multicenter, retrospective review documents the initial experience using the Flex system for transoral surgery in 2 United States academic centers. Methods: All patients who underwent transoral robotic surgery using the Medrobotics Flex Robotic System (Raynham, MA) between September 2015 and May 2017 were reviewed. Rates of successful surgery and complications were evaluated. Results: Thirty‐six men and 32 women were enrolled in the study. The average age was 55.6 years (range 17‐82 years). The Flex system was used successfully in surgery of the tongue base, the palatine tonsils, the supraglottis, the glottis, the hypopharynx, the oral tongue, and the soft palate. Only 6 cases (7.6%) required readmission after discharge. There were no intraoperative or immediate postoperative complications, with no cases of intraoperative hemorrhage. Conclusion: To the best of our knowledge, this is the first study in the United States evaluating the use of the Flex system to safely resect lesions in the oral cavity, larynx, and pharynx.